Pengaruh Penggunaan Pupuk Terhadap Produksi Cabai Merah Besar di Desa Panyusuhan Kecamatan Sukaluyu Kabupaten Cianjur - Zahra, Mayla; Suminartika, Eti (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Large red chili peppers are an important horticultural commodity for the Indonesian economy, but Panyusuhan Village in Cianjur Regency still faces fluctuating productivity and tends to be below the district average. This study aims to analyze the effect of fertilizer use on the production of large red chili peppers with a quantitative approach through a survey of 30 farmers selected through a simple random sampling technique. The data were analyzed using the Cobb-Douglas production function as well as the classical assumption test (R2, F test, and t test). The results of the study showed that the production factors used by farmers were generally in accordance with the recommendations, with an R2 valueof 0.973 which means that the independent variable in the study could explain 97.3% of production variations. The F test showed that all variables had a significant effect simultaneously, while the t test revealed that the NPK fertilizer variable had a partial significant effect, while the manure variable partially had an effect but not significantly on the production of large red chilies.